Analisis Konten TikTok Pandawara Group Tentang Kampanye Lingkungan - Nurrohimah, Aghniya Risky; Istighfarin, Awit; Mukhlisin, Latutik (Universitas Muhammdiyah Yogyakarta, 2026)
This study examines persuasive communication in environmental campaigns initiated by the Pandawara Group account on TikTok in response to the waste crisis. Employing a qualitative approach through content analysis, the research closely analyzes five uploaded videos to identify persuasive techniques based on Aristotle’s classical elements of persuasive communication, namely ethos, pathos, and logos. The findings reveal that Pandawara Group successfully establishes credibility (ethos) through the demonstration of tangible actions and the consistency of its movement. The group also effectively evokes emotional responses (pathos) by employing inspirational narratives and visual representations of environmental impacts, while simultaneously presenting logical arguments (logos) regarding the consequences of waste-related issues and the urgency of public participation. These findings reinforce the proposition that TikTok functions as an effective medium for environmental advocacy due to its capacity to disseminate persuasive messages widely, accurately, rapidly, and emotionally. This study contributes significantly to the enrichment of persuasive communication scholarship in the digital media era, particularly within the context of youth-driven, participatory environmental campaigns.